Digital body language : how to build trust and connection, no matter the distance - Dhawan, Erica (New York : St. Martin's Press, 2021)
"From Erica Dhawan, co-author of Get Big Things Done, the definitive guide to communicating and connecting wherever you are. Email replies that show up a week later. Video chats full of "oops sorry no you go" and "can you hear me?!" Ambiguous text-messages. Weird punctuation you can't make heads or tails of. Is it any wonder communication takes us so much time and effort to figure out? How did we lose our innate capacity to understand each other? Humans rely on body language to connect and build trust, but with most of our communication happening from behind a screen, traditional body language signals are no longer visible -- or are they? In Digital Body Language, Erica Dhawan, a go-to thought leader on collaboration and a passionate communication junkie, combines cutting edge research with engaging storytelling to decode the new signals and cues that have replaced traditional body language across genders, generations, and culture. In real life, we lean in, uncross our arms, smile, nod and make eye contact to show we listen and care. Online, reading carefully is the new listening. Writing clearly is the new empathy. And a phone or video call is worth a thousand emails. Digital Body Language will turn your daily misunderstandings into a set of collectively understood laws that foster connection, no matter the distance. Dhawan investigates a wide array of exchanges-from large conferences and video meetings to daily emails, texts, IMs, and conference calls-and offers insights and solutions to build trust and clarity to anyone in our ever changing world"--
Includes bibliographical references.
Keywords: Communication in organizations; Interpersonal communication; Information technology -- Social aspects; Body language